Influence of alloying elements on cellular response and in-vitro corrosion behavior of titanium-molybdenum-chromium alloys for implant materials - Nor Haliza Mat Baharin; Masfueh Razali; Shahida Mohd-Said; Junaidi Syarif; Andanastuti Muchtar (Elsevier Ireland Ltd, 2024)
Indexed by Scopus